THE EFFECTIVENESS OF INTERACTIVE MULTIMEDIA-BASED LEARNING METHODS TO INCREASE THE MOTIVATION OF ELEMENTARY SCHOOL TEACHERS IN THE JSIT KULONPROGO ENVIRONMENT - Lidyasari, Aprilia Tina; Rokhman, Muhamad Nur; Nugroho, Alifi Nur Prasetia; Anggito, Albi (UIN Sunan Kalijaga Yogyakarta, 2023)
Teachers' motivation in developing multimedia in primary-secondary school teachers who are members of the Kulonprogo integrated Islamic school network is still low. The purpose of this study is to see if there is a significant effect on teacher motivation after providing interactive multimedia training to teachers. Multimedia training includes providing material about interactive multimedia, making multimedia by teachers, mentoring, demonstrations and producing interactive multimedia products from elementary junior high schools. The research method used is a pre-experiment design involving 25 primary-secondary school teachers who are members of the Kulonprogo integrated Islamic school network. The sampling technique used is purposive sampling and uses the Wilcoxon test in data analysis. Activities will be carried out using offline and online methods using a theoretical and practical approach. Theoretical material and practical assistance are carried out in the Kapanewon Kulonprogo area. The implementation of activities will be reflected through an evaluation of the participants' understanding of the material, seen from the performance, work results, program implementation evaluation questionnaire. Training is carried out offline and online. Offline training was held at the Yogyakarta State University Hall, Wates Campus offline and online through the zoomeeting application. The results of the implementation of this training based on the pre-post questionnaire obtained an increase in pre-post results from an average of 58.2 to an average of 69.52. While the results of data processing using SPSS obtained Sig Value. <0.05, this shows that there is a significant effect on teacher motivation before and after the provision of training in making interactive multimedia for teachers. The conclusion of the research is that there is a positive influence on teacher motivation before and after the provision of interactive multimedia training to elementary and junior high school teachers who are members of an integrated Islamic school network in Kulonprogo Regency, Yogyakarta Special Region.